Influence of sowing windows on yield performance, water-use efficiency, and profitability of oilseed crops: INFLUENCE OF SOWING WINDOWS ON YIELD PERFORMANCE, WUE AND PROFITABILITY OF OILSEED CROPS - C RADHA KUMARI; B SAHADEVA REDDY; M VIJAY SANKAR BABU (Journal of Oilseeds Research, 2026)
A field experiment was conducted to evaluate the effect of sowing dates on growth, yield, rainwater-use efficiency, and economics of groundnut (Arachis hypogaea), castor (Ricinus communis), and sesame (Sesamum indicum). The experiment, laid out in a split-plot design with five sowing dates and three replications, revealed that crop duration, rainfall, and rainy days declined with delayed sowing. Early sowing (June 1 FN) produced the highest yields in groundnut (694 kg/ha) and castor (1388 kg/ha), while sesame performed better under mid-season sowings (August-September). Groundnut equivalent yield and economic analysis showed castor as the most productive and profitable crop (mean GEY 962 kg/ha, B:C ratio 3.37), followed by early-sown groundnut, whereas sesame remained uneconomical. Correlation and regression analyses identified filled pods, branches and spikes, and plant height as the major yield determinants in groundnut, castor, and sesame, respectively.